The Owen and Banzhaf–Owen values revisited. (2nd June 2016) - Alonso-Meijide, J.M.; Casas-Méndez, B.; González-Rueda, A.M.; Lorenzo-Freire, S.
Abstract : In this work, we consider games with coalitional structure. We afford two new parallel axiomatic characterizations for the well-known Owen and Banzhaf–Owen coalitional values. Two properties are common to both characterizations: a property of balanced contributions and a property of neutrality. The results prove that the main difference between these two coalitional values is that the former is efficient, while the latter verifies a property of 2-efficiency.